Impact of ranolazine on exercise tolerance and arrhythmias in patients with INOCA - Tseluyko, Vira; Pylova, Tetyana (ScienceRise: Medical Science, 2021)
The aim of the study to evaluate the effect of supplementation of basic therapy by ranolazine in patients with INOCA on exercise test parameters and Holter ECG monitoring. Materials and methods. 53 patients with stable coronary heart disease were examined, including 18 men (33.9 %) and 35 (66 %) women, the average age of patients was 57 (±9.68) years. According to the results of coronary angiography all patients had non-obstructive coronary arteries. In addition to physical and laboratory examination, bicycle ergometry, Holter ECG monitoring and echocardiography were included in the examination of patients. Patients were divided into 2 groups: group I - patients who in addition to standard therapy received ranolazine at a dose of 1000 mg twice a day for 6 months, and group II patients with standard coronary heart disease therapy. After 6 months from the beginning of the observation an objective examination, echocardiography, exercise test, Holter ECG monitoring were repeated. Results. The study found that patients receiving ranolazine in addition to standard therapy had a statistically significant increase in exercise duration after 6 months compared with baseline and group II. Before treatment in group I, the duration of the exercise test was 356.51±180.24s, and after treatment 414.32±142.10s (p=0.03). In group II, the duration of the test before treatment was 361.4±160.24 c, and after 380.5±152.2 s (p=0.15). It was also found that the duration of the test differed significantly in group I after treatment of patients from group II after treatment of patients with a standard treatment regimen (p=0.04). According to the results of Holter ECG monitoring in group I found a positive effect of ranolazine on the frequency of ventricular arrhythmias: before treatment n=1142 [30; 2012], after treatment n=729 [23; 1420], while in group II a significant difference between the number of extrasystoles before treatment and after not detected (n=1026 [17; 1920], n=985 [15; 1680], respectively) p=0.18. Conclusions. The addition of ranolazine to the basic therapy of patients with non-obstructive coronary arteries disease helps to increase exercise tolerance (according to the loading stress test) and contributes to a significant reduction in the number of ventricular arrhythmias (according to Holter-ECG) compared with both baseline and group II